Sinamā lipi - Āriyadāsa, Eḍvin (Divăsa Pracārakayō, 1985)
Transcript of lectures on motion-pictures and television broadcasting in Sri Lanka.
In Sinhalese.
Transcript of lectures on motion-pictures and television broadcasting in Sri Lanka.
Keywords: Television broadcasting / Sri Lanka.; Motion pictures / Sri Lanka.